Trends in the smoking habits of young adults with diabetes. Issue 909 (1st July 2001) - MacFarlane, I; Gill, G; Grove, T; Wallymahmed, M
Abstract : OBJECTIVES: To examine changes in the prevalence of smoking in young adult diabetic patients between 1990 and 1999. SETTING: Walton Diabetes Centre, University Hospital Aintree, Liverpool, UK. DESIGN: Direct questioning as well as the urinary cotinine:creatinine ratio were used to assess the smoking habits of 99 young type 1 diabetic patients in 1991 (mean age 21.5 years, duration of diabetes 7.3 years), and in 112 similar patients in 1999 (mean age 23.4 years, duration of diabetes 9.6 years). RESULTS: The admitted smoking rate was 31/99 (31%) in 1990 compared with 31/112 (28%) in 1999 (not significant). However, in 1990 there were an additional 17 "covert" smokers (patients who denied smoking, but had an unequivocally raised urinary cotinine:creatinine ratio), but only three in 1999 (p<0.05). This gave a corrected validated smoking rate of 48/99 (48%) in 1990 and 34/112 (30%) in 1999, representing a significant fall (p<0.02). CONCLUSION: Smoking rates in young type 1 diabetic patients appear to have fallen during the last decade, and reporting of smoking behaviour is now more honest.